The Influence of Principal and Learning Community Learning Leadership on The Quality of Teacher Learning - Astuti, Kundi; Nurkolis, Nurkolis; Aryanto, Lilik (JURNAL AL-TANZIM, 2025)
This study aims to examine how the principal’s instructional leadership, the learning community, and their interaction affect learning quality. This study uses a quantitative approach with a correlational research design, data collection using psychological scales, and analyses using descriptive statistics, simple linear regression, and multiple regression. The study’s findings show that the principal’s instructional leadership significantly influences the quality of teacher learning, that the learning community has a significant impact on the quality of teacher learning, and that the quality of teacher learning is significantly influenced by both the learning community and the principal’s instructional leadership combined. This study provides implications: increasing quality learning requires synergy between school leadership and community learning; quality learning influences leadership and collaboration that form a culture of productive schools; and the Department of Education and Culture STEM should develop schools’ capacity and strengthen community studies.